2016
DOI: 10.1021/acs.langmuir.6b00763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt on Phosphorylcholine-based Zwitterionic Polymer Brushes

Abstract: A quantitative investigation of the responses of surface-grown biocompatible brushes of poly(2-(methacryloyloxy)ethyl phosphorylcholine) (PMPC) to different types of salt has been carried out using ellipsometry, quartz crystal microbalance (QCM) measurements, and friction force microscopy. Both cations and anions of varying valency over a wide range of concentrations were examined. Ellipsometry shows that the height of the brushes is largely independent of the ionic strength, confirming that the degree of swel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 62 publications
7
77
0
Order By: Relevance
“…A linear friction-load relationship was not observed for any salt at the concentrations used in this work for either experimental geometry. A similar phenomenon was reported in recent work on the effect of salt on the frictional properties of poly[2-(methacryloyloxy)-ethyl phosphorylcholine] (PMPC) which is highly lubricious and generally displayed a linear friction-load relationship [40]. In that particular study, KI was determined to have a larger coefficient of friction than KBr, but that is due to the nature of the interaction between halide anions and the functional groups.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A linear friction-load relationship was not observed for any salt at the concentrations used in this work for either experimental geometry. A similar phenomenon was reported in recent work on the effect of salt on the frictional properties of poly[2-(methacryloyloxy)-ethyl phosphorylcholine] (PMPC) which is highly lubricious and generally displayed a linear friction-load relationship [40]. In that particular study, KI was determined to have a larger coefficient of friction than KBr, but that is due to the nature of the interaction between halide anions and the functional groups.…”
Section: Discussionsupporting
confidence: 84%
“…Recent work has shown that there is a low adhesion regime whereby single asperity contact mechanics is insufficient to describe the interaction of a polymer brush with an AFM tip [11,12,[39][40][41][42][43][44]. The AFM tip can reasonably be considered as a single asperity probe given its small radius.…”
Section: Introductionmentioning
confidence: 99%
“…Zwitterionic polymers, which contain both anionic groups and cationic groups along their molecular chains, play an important role in oil recovery, seawater desalination, sewage treatment, and biomaterials, enhancing their performance in saline water . For polyzwitterions, ionic groups can be either divided into different monomer units or concentrated in the same monomer unit.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be mimicked by end-anchoring polymers to surfaces to form so-called polymer brushes [4]. With these brushes, effective and durable lubricants have been developed that can work under aqueous [5,6] as well as oil environments [7].…”
Section: Introductionmentioning
confidence: 99%